Awareness and Skillfulness in Using Arabic Language Instructional Software Among Senior Secondary Schools in Kwara State - Sanusi, Taofeeq Olamilekan (Journal of Islamic Education and Pedagogy, 2025)
The study examined awareness and skillfulness in using Arabic Instructional software among senior secondary schools in Kwara state. A descriptive survey research design was used. Arabic language teachers were the respondents. There were 146 Arabic language teachers in Kwara State (Kwara State Teaching Service Commission, 2023). A sample of 108 Arabic language teachers was selected using the Kredjcie and Morgan sample size determination table. The research instrument is "Awareness and Skillfulness in Using Instructional Software Questionnaire (ASUISQ)". Findings showed that there is low awareness of Arabic language Instructional software among the majority of Arabic teachers in senior secondary schools in Kwara state is relatively low. The study indicates low skillfulness in using Arabic language Instructional software among Arabic teachers in senior secondary schools in Kwara state. Based on the results, there is low awareness of Verbace Arabic-English Offline Dictionary, Best Arabic Calligraphy and Weyyak Arabic Library Software, SHAHID Arabic Video Streaming App and Smart 13rab Software as instructional software among Arabic teachers in senior secondary schools in Kwara state is relatively low. The study also concluded that there is low skillfulness of Verbace Arabic-English Offline Dictionary, best Arabic Calligraphy and Weyyak Arabic Library Software, SHAHID Arabic Video Streaming App and Smart 13rab Software as instructional software among Arabic teachers in senior secondary schools in Kwara State. The study also recommended that the Kwara State Ministry of Education make adequate budgetary allocations for in-service training, particularly on modern instructional software.